Three-phase oil-immersed distribution transformers 50 Hz, from 50 kVA to 2500 kVA with highest voltage for equipment not exceeding 36 kV. Requirements and tests concerning pressurised corrugated tanks Part 4, (31st December 2011) - British Standards Institution,
No abstract available